Case report: Novel use of the conventional method- chemical nail avulsion may be effective for treatment of green nail syndrome - Yu, Qian; Wang, Yuanyuan; Yang, Hong; Li, Wei; Yang, Lianjuan (Frontiers in Medicine, 2022)
Green nail syndrome (GNS) is a triad of green discoloration of the nail plate, proximal paronychia, and distal onycholysis. Pseudomonas aeruginosa is the most common causative agent. There is no unified standard for the diagnosis and treatment of GNS. Thus, the treatment of GNS is challenging and often refractory. We report three representative cases with different predisposing factors, including trauma-related GNS, occupation-related GNS and onychosis-related GNS. The patients with GNS accompanied by onycholysis were instructed to undergo chemical nail avulsion combined with topical antibiotics. Favorable curative effects were observed in all cases. Chemical nail avulsion with urea powder, as a conventional method, may be an effective method for the treatment of GNS and deserves to be clinically generalized.